Learning IBM Watson analytics : make the most advanced predictive analytical processes easy using Watson analytics with this easy-to-follow practical guide /: make the most advanced predictive analytical processes easy using Watson analytics with this easy-to-follow practical guide. ([2016]) - (Software consultant), Miller, James D
No abstract available